Studi Literatur tentang Faktor-Faktor yang Mempengaruhi Kemunduran Pendidikan Islam - Mardinal Tarigan; Sella Monica; Dhea Alfira (Jurnal Dirosah Islamiyah, 2024)
Uu's research investigates changes and setbacks in Islamic education from its heyday to contemporary times. The research methodology used is a Literature Study/Library Study approach, by collecting data from various sources such as digital libraries and the internet. Analysis was carried out on the factors that influenced the decline of Islamic education, including the tendency of excessive philosophy, lack of appreciation for scientists, internal and external conflicts, as well as the impact of Mongol attacks and the Crusades. The results of the research showed that the decline of Islamic education had significant impacts such as stagnation in motivation, a decline in the quality of education and intellectual thinking and a narrowing of the curriculum in madrasas. However, efforts to purify Islamic teachings in the eighteenth century gave hope for a more progressive renewal of Islamic education